Government Subsidies and Business Resilience of Chinese Electric Vehicle Enterprises: The Roles of ESG and Technological Capability - Qiu Zhao; Chao Zhang; Zhuoqian Li (Energies)
In the context of increasing global macroeconomic policy uncertainty, the effectiveness of Chinese government subsidies in promoting the business resilience of electric vehicle (EV) enterprises and the sustainable development of the EV industry has attracted significant attention. This paper utilizes panel data from Chinese listed EV companies from 2013 to 2022 to examine the impact of government subsidies on the business resilience of these enterprises. It also analyzes the moderating roles of corporate ESG (Environmental, Social, and Governance) performance and technological capability. This study finds that government subsidies significantly enhance business resilience, particularly for companies with a high ESG performance and a strong technological capability, which can better leverage these subsidies to further enhance their resilience amidst market fluctuations and uncertainties. Moreover, as an external support measure, government subsidies complement internal corporate factors like ESG performance and technological capability, promoting the sustainable development of the industry. Policymakers should consider corporate ESG performance and technological capability when designing subsidy programs to maximize their effectiveness.